Kolaborasi Lintas Sektor dalam Program “Denting Nusantara” sebagai Upaya Penurunan Angka Stunting di Pluit, Jakarta Utara - Dityan Satyayoni; Monica Anindita F; Sarika Apriyeni G; Vowas Gamar B (Journal on Education, 2023)
to increase the health status and nutritional status of the community through health efforts and community empowerment supported by financial protection and equity in health services. The approach used in this study is a qualitative case study design. Data collection techniques using observation and interviews. The data used is the result of the interview. The whole series of "Denting Nusantara" activities received support from the local government, such as the Pluit Urban Village Head, Penjaringan District Head, to other strategic actors within the Penjaringan District. The launching of the "Denting Nusantara" program was inaugurated by the Mayor of North Jakarta City and also the Senior Manager of PT PLN Nusantara Power UP Muara Karang. There are two data references that can be used as indicators for measuring the success of the "Denting Nusantara" program, namely stunting toddler detection data and monitoring results from interventions that have been carried out. There is an increase in the detection rate of stunting under five, this shows that "Denting Nusantara" is proven to be able to detect more effectively with a wider range and through more accurate anthropometric standards